The Development of Fine Surface Roughness of FeCrAl Substrate by Gamma Alumina Coating Material Through Nickel Oxide Catalyst - Dafit Feriyanto; S.S. Abdulmalik; Hadi Pranoto; Supaat Zakaria (International Journal of Advanced Technology in Mechanical, Mechatronics and Materials, 2021)
The most commonly used method for protecting atmospherically exposed steel against corrosion, is the application of protective organic coating systems. It is widely recognized that the stability of the coating-substrate interface is related to the interfacial adhesion forces and electrochemical properties of this region. This study aim to develop fine surface roughness by ultrasonic and electroplating coating methods that applied for FeCrAl catalytic converter. This method consists of thwo methods which are ultrasonic bath that carried out by frequency of 35 kHz and various ultrasonic times of 1, 1.5, 2, 2.5 and 3 hours is imposed and the electroplating was conducted for several variation times of 15, 30, 45, 60 and 75 minutes, current density of 8 A/dm2. The result shows that the surface roughness of UB samples in between 0.11 to 0.21 µm, UBdEL samples of 0.81 to 2.17 µm, UB+EL samples of 0.64 to 1.63 µm and EL samples of 0.69 to 1.11 µm. The finest surface of each techniques are located at UB 1.5 h, UBdEL 45 minutes, UB 1.5 h+EL 30 minutes and UB 30 minutes. That data is supported by coating thickness of coated FeCrAl substrate where UB samples in between 2 -2.8 µm, UBdEL samples of 4.1 to 5 µm, UB+EL samples of 9.1 to 12 µm and EL samples of 6.2 to 11.3 µm.